Raw material composition of quasi-solid electrolyte, quasi-solid electrolyte, lithium battery and preparation method and application of lithium battery

By using a raw material composition of quasi-solid electrolyte in lithium-ion secondary batteries, the polymer network and SEI layer are generated, which solves the problem of insufficient thermal stability and interface compatibility of traditional batteries at high temperatures, and achieves high energy density and high Safe lithium battery.

CN119297387APending Publication Date: 2025-01-10BEIJING UNIV OF CHEM TECH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411315323.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-06-11
Filing Date
2024-09-20
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Traditional lithium-ion secondary batteries have shortcomings in energy density and safety, especially the problems of poor thermal stability and low interface compatibility, which lead to short circuits and safety hazards at high temperatures.

Method used

Using a quasi-solid electrolyte raw material composition, including in-situ polymeric monomers, lithium salts, solvents, additives and initiators, by forming a polymer network and SEI layer on the surface of lithium metal, reduces the interface impedance and forms a protective layer at high temperatures. Prevent the electrode from contacting the electrolyte directly.

Benefits of technology

It significantly improves the thermal safety performance and impact resistance of lithium batteries, ensures that there is no short circuit or explosion after thermal shock at 200℃, and provides a lithium-ion secondary battery with high energy density and high safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297387A_ABST
    Figure CN119297387A_ABST
Patent Text Reader

Abstract

The invention discloses a raw material composition of a quasi-solid electrolyte, the quasi-solid electrolyte, a lithium battery and a preparation method and application of the lithium battery. The raw material composition of the quasi-solid electrolyte comprises the following raw materials: an in-situ polymerization monomer, a lithium salt, an optional solvent, an optional additive and an initiator. According to the invention, the quasi-solid-state polymer electrolyte capable of in-situ polymerization is designed, and the organic-inorganic composite coating diaphragm and the metal lithium negative electrode are connected in parallel, so that the lithium ion secondary battery with high specific energy and thermal shock resistance is obtained. The liquid phase component contained in the electrolyte ensures the interface wettability, the interface impedance after polymerization is effectively reduced, and the battery can normally operate at high temperature. When matched with a diaphragm, a positive electrode and a negative electrode for use, the thermal runaway temperature of the battery is effectively increased, and the battery does not have short circuit, explosion and combustion after thermal shock at 200 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion secondary batteries, and more particularly to a raw material composition of a quasi-solid electrolyte, a quasi-solid electrolyte, a lithium battery, and a preparation method and application thereof. Background Art

[0002] With the rapid development of new fields such as electric vehicles, robots, and drones, the demand for lithium-ion secondary batteries with both high energy density and high safety is becoming more and more urgent. In terms of energy density, the energy density of traditional lithium-ion secondary batteries with graphite as the negative electrode is difficult to exceed 400Wh Kg -1 Since the metallic lithium anode has a high theoretical specific capacity (3860 mAh g -1 ) and the lowest electrochemical reduction potential (-3.04V vs. standard hydrogen electrode), so that lithium batteries with metallic lithium as negative electrode can reach more than 400Wh Kg -1 energy density, meeting the demand for high energy density in new fields. In terms of safety, the multi-scenario application of lithium-ion batteries also puts forward new requirements for the thermal shock resistance of diaphragms and electrolytes.

[0003] Traditional polyethylene (PE) diaphragms have poor thermal stability, low mechanical strength, and severe thermal shrinkage at high temperatures, which can easily cause safety hazards such as short circuits. Some solvents in traditional ether-based and ester-based liquid electrolytes have low flash points and boiling points, and are prone to gas generation when heated, causing safety hazards.

[0004] Researchers have increased the thermal shrinkage temperature of the diaphragm by coating it with ceramic electrolytes (such as patent CN114156602A) and aramid (PPTA, such as patent CN112751135A), but simple diaphragm modification cannot solve the thermal safety problem of the battery as a whole. Ceramic-based electrolytes have high thermal stability but poor interface compatibility, while in-situ polymer-based solid electrolytes (such as patent CN 109818055A) have both high safety and high interface compatibility, but low ionic conductivity at room temperature.

[0005] In summary, only by developing electrolytes with better performance and further coordinating the overall design of electrode materials, separators and electrolytes can we obtain lithium-ion secondary batteries with both high energy density and high safety. Summary of the invention

[0006] In order to solve the problems in the prior art, the present invention proposes a raw material composition of a quasi-solid electrolyte, a quasi-solid electrolyte, a lithium battery and a preparation method and application thereof. The quasi-solid electrolyte raw material composition of the present invention is used as an electrolyte. After being assembled into a lithium metal battery, some monomers undergo anionic polymerization to generate a polymer network on the surface of the lithium metal; at the same time, multiple lithium salt solutes (i.e., lithium salts), additives, initiators and solvents are filled therein to form a quasi-solid electrolyte in situ; the liquid phase components contained in the electrolyte ensure the wettability of the interface and effectively reduce the interface impedance after polymerization; and the battery can also operate normally at high temperatures. At high temperatures, due to the decomposition of the initiator to generate free radicals, the remaining monomers are rapidly polymerized into a polymer protective layer to prevent internal short circuits and cut off direct contact between the electrode and the electrolyte. When the quasi-solid electrolyte of the present invention is used in conjunction with a diaphragm and a positive and negative electrode, the thermal runaway temperature of the battery is effectively increased, and the battery does not short-circuit, explode or burn after a thermal shock of 200°C. The thermal safety performance and impact resistance of the lithium battery prepared by the present invention are greatly improved.

[0007] One of the purposes of the present invention is to provide a raw material composition for a quasi-solid electrolyte, comprising raw materials of the following components: an in-situ polymerization monomer, a lithium salt, an optional solvent, an optional additive, and an initiator; wherein:

[0008] The content of the in-situ polymerized monomer is 20 to 75 wt %;

[0009] The content of the solvent is 0 to 40 wt%;

[0010] The content of the initiator is 0.05 to 5 wt%;

[0011] The content of lithium salt is 6 to 25 wt%;

[0012] The content of the additive is 0 to 30 wt%.

[0013] In the raw material composition of the quasi-solid electrolyte of the present invention, preferably,

[0014] In the raw material composition of the quasi-solid electrolyte,

[0015] The content of the in-situ polymerized monomer is 30 to 75 wt %;

[0016] The content of the solvent is 0 to 40 wt%;

[0017] The content of the initiator is 0.05 to 5 wt%;

[0018] The content of lithium salt is 6 to 25 wt%;

[0019] The content of the additive is 0 to 30 wt%;

[0020] Preferably,

[0021] The content of the in-situ polymerized monomer is 34 to 72 wt%;

[0022] The content of the solvent is 0 to 10 wt%;

[0023] The content of the initiator is 0.05 to 1 wt%;

[0024] The content of lithium salt is 10-25wt%;

[0025] The content of the additive is 2 to 15 wt%.

[0026] In the raw material composition of the quasi-solid electrolyte of the present invention, preferably,

[0027] The in-situ polymerization monomer is selected from one or more of acrylate monomers; preferably, the in-situ polymerization monomer is selected from one or more of ethoxylated trimethylolpropane triacrylate, polyethylene glycol methyl ether methacrylate, polyethylene glycol diacrylate, polyethylene glycol methacrylate, 2,2,3,3,3-pentafluoropropyl acrylate; further preferably, the in-situ polymerization monomer is selected from a mixture of polyethylene glycol methyl ether methacrylate and 2,2,3,3,3-pentafluoropropyl acrylate; and / or,

[0028] The content of the in-situ polymerized monomer is 30 to 40 wt%; and / or,

[0029] The content of the solvent is 0 to 30 wt %; and / or,

[0030] The content of the initiator is 0.05 to 1 wt %; and / or,

[0031] The content of lithium salt is 15-25wt%; and / or,

[0032] The content of the additive is 1 to 25 wt%.

[0033] In the raw material composition of the quasi-solid electrolyte of the present invention, for example

[0034] The content of the in-situ polymerized monomer is 20wt%, 25wt%, 30wt%, 34wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt% and a parameter range consisting of any two of the above values;

[0035] The content of the solvent is 0wt%, 0.4wt%, 5wt%, 8wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt% and a parameter range consisting of any two of the above values;

[0036] The content of the initiator is 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.8wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% and a parameter range consisting of any two of the above values;

[0037] The content of lithium salt is 6wt%, 8wt%, 10wt%, 11wt%, 12wt%, 15wt%, 19wt%, 20wt%, 21wt%, 25wt% and a parameter range consisting of any two of the above values;

[0038] The content of the additive is 0wt%, 2wt%, 5wt%, 8wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt% and a parameter range consisting of any two of the above values.

[0039] In the raw material composition of the quasi-solid electrolyte of the present invention, preferably,

[0040] The lithium salt is selected from lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluoromethanesulfonyl)imide (LiFSI), lithium nitrate (LiNO 3 ), at least one of lithium difluorooxalatoborate (LiDFOB) or lithium bis(oxalatoborate) (LiBOB); preferably, the lithium salt is a mixture of lithium bis(trifluoromethanesulfonyl imide) or lithium difluorooxalatoborate and lithium nitrate; and / or,

[0041] The boiling point of the solvent is ≥200°C; preferably, the solvent is selected from at least one of ethylene carbonate (EC), propylene carbonate (PC) or fluorocarbonate (FEC); and / or,

[0042] The additive is selected from at least one of succinonitrile (SN), vinylene carbonate (VC), 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl imide) or 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl imide); preferably, the additive is selected from a mixture of succinonitrile and vinylene carbonate; and / or,

[0043] The initiator is selected from at least one of 1-((cyano-1-methylethyl)azo)formamide (CMAB), azobisisobutyronitrile (AIBN) or dibenzoyl peroxide (BPO).

[0044] The second object of the present invention is to provide a method for preparing a quasi-solid electrolyte raw material composition, comprising the following steps:

[0045] In a protective atmosphere, a polymerization monomer, an optional solvent, an optional additive lithium salt and an initiator are mixed, and stirred uniformly at room temperature to obtain a quasi-solid electrolyte raw material composition (i.e., an electrolyte solution);

[0046] Preferably, the quasi-solid electrolyte raw material composition described in one of the objectives of the present invention is prepared by using the above method.

[0047] In the present invention, the quasi-solid electrolyte raw material composition does not react after mixing. After being added as an electrolyte to a lithium battery, it will polymerize under the initiation of the negative lithium plate to form a quasi-solid electrolyte.

[0048] In the present invention, adding the raw materials in the quasi-solid electrolyte raw material composition separately or together has no obvious effect on the experimental results, which is only a consideration of experimental habits or operational convenience.

[0049] One of the objectives of the present invention is to provide a quasi-solid electrolyte, which is prepared by reacting the quasi-solid electrolyte raw material composition described in one of the objectives of the present invention or the quasi-solid electrolyte raw material composition prepared by the method described in the second objective of the present invention.

[0050] One of the objectives of the present invention is to provide an application of the quasi-solid electrolyte raw material composition described in one of the objectives of the present invention or the quasi-solid electrolyte described in the third objective of the present invention in a lithium battery.

[0051] One of the objectives of the present invention is to provide a lithium battery, which includes a negative electrode material, a positive electrode material, the quasi-solid electrolyte described in the third objective of the present invention, and a separator.

[0052] In the lithium battery described in the present invention, the negative electrode material, the positive electrode material, and the separator used in the invention are all commonly used existing materials; preferably,

[0053] The positive electrode material includes one of a high-nickel ternary positive electrode and a lithium-rich manganese-based oxide positive electrode material; preferably, the high-nickel ternary positive electrode is selected from NCM622 and NCM811; the lithium-rich manganese-based oxide is selected from xLi 2 MnO 3 -(1 - x)LiTMO 2 ; where 0 < x < 1, TM is Ni, Co or Mn; and / or,

[0054] The negative electrode material is a metallic lithium plate; and / or,

[0055] The separator is at least one of a polyethylene (PE) membrane, a polypropylene (PP) separator, a PP / PE / PP membrane, a polyimide separator, a ceramic-coated separator, or a poly-p-phenyleneterephthalamide-coated separator (PPTA@PP).

[0056] One of the objectives of the present invention is to provide a preparation method for the lithium battery described in the fifth objective of the present invention, including the following two methods:

[0057] Method 1: The preparation of button lithium battery includes the following steps:

[0058] The batteries are stacked in the order of negative electrode shell-spring sheet-gasket-negative electrode sheet-diaphragm-positive electrode sheet-positive electrode shell, and the quasi-solid electrolyte raw material composition prepared by the method according to the first object of the present invention or the quasi-solid electrolyte raw material composition prepared by the method according to the second object of the present invention is added to both sides of the diaphragm, and packaged to obtain a button-type lithium battery;

[0059] Method 2: The preparation of soft-pack lithium battery includes the following steps:

[0060] First, the positive electrode sheet and the negative electrode sheet are cut, and the tabs are connected to the positive and negative electrodes by spot welding. Then, the negative electrode, the separator and the positive electrode are tightly fitted, and the battery cell is sealed in an aluminum-plastic film by heat sealing. Finally, the quasi-solid electrolyte raw material composition prepared by the method described in one of the purposes of the present invention or the quasi-solid electrolyte raw material composition prepared by the method described in the second purpose of the present invention is injected, and after packaging, the quasi-solid electrolyte raw material composition is allowed to stand and formed to complete the preparation of the soft-pack battery.

[0061] The raw material composition of the quasi-solid electrolyte of the present invention, after being added as an electrolyte into a lithium battery, will polymerize under the initiation of the negative electrode lithium sheet to form a quasi-solid electrolyte; in addition, the lithium salt, some solvents, etc. in the electrolyte can form a stable SEI layer to hinder electronic conduction, thereby alleviating the anion polymerization of the electrolyte triggered by the lithium metal surface, and avoiding the adverse effect of excessive polymerization on the electrolyte ion conduction; at the same time, the SEI layer itself as Li + The excellent conductor can improve the transmission dynamics and avoid the formation of lithium dendrites. The in-situ polymerization of the electrolyte ensures close contact between the electrode and the electrolyte, which can help Li+ migrate at the electrode / electrolyte interface. The introduction of solvents and / or additives greatly reduces the crystallinity of the polymer (too high crystallinity is not conducive to the mobility of the polymer conductive chain segment and directly affects the ionic conductivity of the electrolyte), which helps to construct Li + Fast conduction channels, enhancing Li + Under high temperature or extreme thermal shock conditions, the initiator decomposes rapidly, further initiating the polymerization of monomers in the electrolyte, increasing the degree of solidification, cutting off direct contact between the electrode and the electrolyte, preventing internal short circuits, and greatly improving the thermal safety and impact resistance of the battery.

[0062] In summary, the present invention provides a method for preparing a lithium-ion secondary battery with both high energy density and high safety. The present invention obtains a lithium-ion secondary battery with high specific energy and resistance to thermal shock by designing a quasi-solid polymer electrolyte that can be polymerized in situ, and using an organic-inorganic composite coated diaphragm and a metal lithium negative electrode in parallel. The liquid phase components contained in the electrolyte ensure the wettability of the interface, effectively reduce the interface impedance after polymerization, and the battery can also operate normally at high temperatures. When used in conjunction with the diaphragm and the positive and negative electrodes, the thermal runaway temperature of the battery is effectively increased, and the battery does not short-circuit, explode, or burn after a thermal shock of 200°C.

[0063] The endpoints and any values ​​of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, the endpoint values ​​of each scope, the endpoint values ​​of each scope and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.

[0064] Beneficial effects:

[0065] The present invention designs a quasi-solid electrolyte that can be polymerized in situ. With the cooperation of various components, in-situ interfacial local polymerization initiated by lithium metal is achieved at room temperature. Under high temperature conditions, further polymerization is induced by heat under the action of an initiator, and a polymer protective layer can be quickly polymerized at high temperature to prevent internal short circuits and cut off direct contact between electrodes and electrolytes. In addition, when components such as solvents and additives are introduced, the polymerization behavior can be adjusted, the crystallinity can be reduced, the temperature range of use can be widened, the ionic conductivity and interfacial compatibility of the electrolyte can be improved, and the excellent comprehensive performance of the electrolyte can be ensured. On this basis, with a diaphragm with good heat resistance, a high energy density positive and negative electrode, and the synergistic effect of various battery components, new insights are provided for the future application prospects of high-performance and high-safety lithium secondary batteries. The present invention provides an overall preparation scheme for a heat-resistant lithium metal battery, and the preparation of a lithium battery has the characteristics of high energy density and high safety. In particular, when the quasi-solid electrolyte of the present invention is used in a lithium battery and the diaphragm is coated with poly(p-phenylene terephthalamide), severe internal short circuits under thermal abuse can be prevented, and excellent thermal safety is achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 The first cycle charge and discharge curve of the button lithium battery prepared in Example 1 of the present invention at room temperature and 80° C. at a rate of 0.2C;

[0067] Figure 2 is a graph showing the results of Example 1 of the present invention and Comparative Example 1 after being subjected to a 200°C thermal shock, wherein Figure 2 The left figure is the result of Example 1. Figure 2 The right figure is the result of Example 1;

[0068] Figure 3 is a field emission scanning electron microscope (FESEM) image of the surface of the PPTA@PP separator used in Example 2 of the present invention;

[0069] Figure 4 is the thermal shrinkage of the quasi-solid electrolyte used in Example 2 of the present invention when used in combination with different separators at high temperatures;

[0070] Figure 5 is the thermogravimetric analysis test result of the quasi-solid electrolyte used in Example 1 of the present invention;

[0071] Figure 6 is the AC impedance spectrum of the soft-pack lithium battery prepared in Example 2 of the present invention at room temperature;

[0072] Figure 7 This is a graph showing the results of a thermal shock test of a soft-pack lithium battery prepared in Example 2 of the present invention;

[0073] Figure 8 is a charge and discharge curve diagram of a soft-pack lithium battery prepared in Example 2 of the present invention;

[0074] Fig. 9 This is the first cycle charge and discharge curve of the button lithium battery prepared in Example 3 of the present invention at room temperature and 80° C. at a rate of 0.2C. DETAILED DESCRIPTION

[0075] The present invention is described in detail below in conjunction with specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.

[0076] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0077] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0078] The raw materials and reagents used in the following examples are all commercially available or can be prepared by known methods.

[0079] Example 1

[0080] Preparation of raw material composition of quasi-solid electrolyte:

[0081] Under argon atmosphere, 0.688 g LiTFSI and 0.100 g LiNO were first added to a glass sample bottle. 3 Dissolve in a mixed solution of 2 mL (2.16 g) of polyethylene glycol methyl ether methacrylate and 400 μL (0.528 g) of 2,2,3,3,3-pentafluoropropyl acrylate, stir magnetically to dissolve, add 117 μL (0.159 g) of vinylene carbonate, and finally add 18 mg of 1-((cyano-1-methylethyl)azo)formamide (CMAB) to form a transparent and uniform solution for use as an electrolyte.

[0082] Preparation of lithium battery:

[0083] A metal lithium sheet was selected as the negative electrode of the battery, NCM811 was selected as the positive electrode, a commercially available Celgard 2325 diaphragm (PP / PE / PP) was used as the diaphragm, the electrolyte prepared as described above was used as the electrolyte of the lithium battery, and the sheets were stacked in the order of negative electrode shell-spring sheet-gasket-negative electrode sheet-electrolyte-diaphragm-electrolyte-positive electrode sheet-positive electrode shell, and a button lithium battery was obtained after packaging. The entire assembly process was completed in a glove box filled with argon.

[0084] Figure 1 middle, Figure 1 a is the result of the constant current charge and discharge test of the above battery using the charge and discharge instrument. The test temperature is room temperature, the test voltage range is 3-4.3V, the charge and discharge rate and battery capacity are calculated based on the mass of NCM811, and the current is set to 0.2C (1C = 190mAh g -1 ) for constant current charge and discharge, the first cycle charge and discharge capacity can reach 180mAh g -1 . Figure 1 b is to raise the test temperature to 80°C, leave it for 7 hours, and then conduct constant current charge and discharge test. Due to the decomposition of the initiator, the generated free radicals induce the monomer to polymerize completely, but the battery still has only 140mAh g -1 discharge capacity.

[0085] Figure 2 The thermal shock test results of the battery and the button battery in comparative example 1 were performed at 5°C min -1 The heating rate is from room temperature to 200℃ and kept for 30min. Figure 2 The left figure is the result of Example 1. Figure 2The figure on the right is the result of Example 1; it can be found that the battery of Comparative Example 1 has gas leakage due to the use of traditional ester electrolyte, which brings great safety hazards, while the quasi-solid electrolyte of the present invention is applied to lithium batteries, and with the cooperation of various components, in-situ interfacial local polymerization initiated by lithium metal is realized at room temperature, and further polymerization is induced by heat under high temperature conditions. Further polymerization can make the electrolyte fully solidified and prevent direct contact between the positive and negative electrodes. The battery prepared therefrom has good thermal safety.

[0086] The quasi-solid electrolyte prepared above was subjected to a thermogravimetric analysis test: a quantitative sample was weighed, and the temperature was raised from room temperature to 600°C under nitrogen conditions at a heating rate of 10°C min -1 , the results are as follows Figure 5 As shown: this electrolyte only undergoes significant decomposition at 300°C, and compared with commercial ester electrolytes (whose thermal decomposition temperature is about 120°C), it has good thermal stability.

[0087] Example 2

[0088] Preparation of quasi-solid electrolyte:

[0089] Under argon atmosphere, 2 mL (2.16 g) of polyethylene glycol methyl ether methacrylate and 400 μL (0.528 g) of 2,2,3,3,3-pentafluoropropyl acrylate were first added to a glass sample bottle, followed by 0.758 g of succinonitrile. After mixing, 0.9098 g of LiTFSI and 0.100 g of LiNO were added. 3 After dissolving by magnetic stirring, 0.216 g of vinylene carbonate was added, and finally 18 mg of CMAB was added to form solution A.

[0090] 0.187 g of LiFSI and 0.287 g of LiTFSI were dissolved in 2 mL of FEC to form solution B, and solution A and solution B were mixed in a mass ratio of 7:3 to obtain a quasi-solid electrolyte.

[0091] Preparation of button lithium battery:

[0092] Same as above-mentioned embodiment 1.

[0093] The battery was tested with a charge and discharge meter. The first cycle discharge capacity reached 193 mAh g at a constant current rate of 0.2 C at room temperature. -1 .

[0094] Preparation of soft pack lithium battery:

[0095] First, weld the positive electrode sheet NCM811 to the tab, and tightly fit the negative lithium sheet, PPTA@PP separator, and positive electrode in a glove box filled with argon. Seal the battery cell in an aluminum-plastic film through heat sealing. After liquid injection and packaging, let it stand and form, and the preparation of the soft-pack lithium battery is completed.

[0096] Figure 3 This is a FESEM image of the surface of the PPTA@PP separator used in Example 2. The presence of the PPTA nanofiber layer plays an important role in eliminating the heat resistance risk of the separator.

[0097] Figure 4 These are the results of thermal shrinkage tests after the quasi-solid electrolyte in Example 2 was coated on the Celgard 2325 separator and the PPTA@PP separator. The QSS@PPTA@PP (QSS@PPTA@PP refers to a polyaramid separator coated with a quasi-solid electrolyte) used in conjunction with the quasi-solid electrolyte will not shrink significantly even when maintained at 200°C for 30 minutes, and has excellent thermal stability.

[0098] Figure 6 This is the AC impedance test result of the soft-pack battery in Example 2, which has a small interface impedance, indicating that the SEI interface of the battery is stable and has excellent lithium ion transmission ability.

[0099] Figure 8 The charge and discharge results of the soft-pack battery in Example 2 at a charge rate of 0.2C at room temperature, the discharge capacity is about 10mAh, and the coulomb efficiency is close to 100%; after being fully charged, a high-temperature storage test is performed, and the results are as follows Figure 7 As shown in a, after being kept at 80℃ for 8h and then taken out, the battery still has a voltage of more than 4V, which proves that the battery will not undergo obvious chemical self-discharge at high temperature and has the potential for high temperature application. -1 The heating rate was raised to 200°C and kept at this temperature for 30 minutes. Figure 7 As shown in b, no battery fire, explosion or leakage was observed after the battery was removed, and the voltage close to 1V proved that the battery was not short-circuited and had high safety.

[0100] Example 3

[0101] Under an argon atmosphere, 0.574 g of LiTFSI was first dissolved in 2 mL of ethoxylated trimethylolpropane triacrylate (2.24 g) in a glass sample bottle and stirred magnetically to form solution A; 0.574 g of LiTFSI was dissolved in 2 mL of a mixed solvent (2.24 g), wherein the proportion of each component of the mixed solvent was DEC:DMC:EC=1:1:1 Vol%, and after dissolution, solution B was formed. 0.5 g of solution A was mixed with 0.7 g of solution B, and 0.005 g of initiator AIBN was added to form a transparent and uniform solution for use as an electrolyte.

[0102] Preparation of lithium battery:

[0103] A metal lithium sheet was selected as the negative electrode of the battery, NCM811 as the positive electrode, a commercially available Celgard 2325 separator (PP / PE / PP) was used as the separator, and the prepared electrolyte was used as the electrolyte of the lithium battery. The sheets were stacked in the order of negative electrode shell-spring sheet-gasket-negative electrode sheet-electrolyte-separator-electrolyte-positive electrode sheet-positive electrode shell, and a button lithium battery was obtained after packaging. The entire assembly process was completed in a glove box filled with argon.

[0104] Fig. 9 The results of the constant current charge and discharge test of the above battery using a charge and discharge instrument. When the constant current charge and discharge is performed at a rate of 0.2C at room temperature, the first cycle discharge capacity reaches 162mAh g -1 . Figure 1 b: After the test temperature is raised to 80°C, it is left for 7 hours before constant current charge and discharge test. The discharge capacity of the first cycle is 76 mAh g -1 , while the battery in Comparative Example 3 without adding any solvent or additive does not have the charge and discharge capability.

[0105] Example 4

[0106] Under argon atmosphere, 0.336 g LiDFOB and 0.078 g LiNO 3 Dissolve in a mixed solution of 2 mL (2.16 g) polyethylene glycol methyl ether methacrylate and 400 μL (0.528 g) 2,2,3,3,3-pentafluoropropyl acrylate, stir and dissolve, then add 0.216 g vinylene carbonate and 18 mg CMAB, and completely dissolve to form solution A. Dissolve 0.287 g LiDFOB in 2 mL FEC to form solution B, mix solution A and solution B in a mass ratio of 7:3, and add to obtain a quasi-solid electrolyte.

[0107] Preparation of lithium battery:

[0108] A metal lithium sheet was selected as the negative electrode of the battery, NCM811 was selected as the positive electrode, a commercially available Celgard 2325 separator was used, and the prepared electrolyte was used as the electrolyte of the lithium battery. The assembly operation of the button lithium battery was the same as that of Example 1.

[0109] The battery was tested with a charge and discharge meter at a constant current. The discharge capacity of the first cycle reached 191 mAh g at a rate of 0.2 C at room temperature. -1 .

[0110] The battery was placed at 80°C for 10 hours and then taken out. When the charge and discharge test was performed at room temperature at a rate of 0.2C, it still had a capacity of 163 mAh g -1 discharge capacity.

[0111] Example 5

[0112] Under argon atmosphere, 0.5 g of succinonitrile was dissolved in a mixed solution of 2 mL of polyethylene glycol methyl ether methacrylate (2.16 g), 400 μL of 2,2,3,3,3-pentafluoropropyl acrylate (0.528 g), and 0.076 g of vinylene carbonate. 0.408 g of LiDFOB and 0.078 g of LiNO were added to the mixed solution. 3 Finally, 7.5 mg CMAB was added and completely dissolved to obtain a quasi-solid electrolyte.

[0113] Preparation of lithium battery:

[0114] A metal lithium sheet was selected as the negative electrode of the battery, NCM811 was selected as the positive electrode, a commercially available Celgard 2325 separator was used, and the prepared electrolyte was used as the electrolyte of the lithium battery. The assembly operation of the button lithium battery was the same as that of Example 1.

[0115] The results of the constant current charge and discharge test of the above battery using the charge and discharge instrument show that when the constant current charge and discharge is performed at a rate of 0.2C at room temperature, the first cycle discharge capacity reaches 194mAh g -1 .

[0116] The battery was placed at 80°C for 10 hours and then taken out. When the charge and discharge test was performed at room temperature at a rate of 0.2C, it still had a capacity of 183 mAh g -1 discharge capacity.

[0117] Comparative Example 1

[0118] Preparation of lithium battery:

[0119] A metal lithium sheet was selected as the negative electrode, NCM811 as the positive electrode, Celgard 2325 as the separator, and an ester electrolyte (LiTFSI in diethyl carbonate (DEC): dimethyl carbonate (DMC): ethylene carbonate (EC) = 1:1:1 Vol% with 5% FEC, specifically: equal volumes of DEC, DMC, and EC solvents were mixed, a certain amount of LiTFSI was added to prepare a 1 mol / L solution, and then a certain amount of fluorocarbonate (FEC) was added so that the mass proportion of the FEC component was 5% of the total volume) as the electrolyte of the lithium battery. The negative electrode shell-spring sheet-gasket-negative electrode sheet-electrolyte-diaphragm-electrolyte-positive electrode sheet-positive electrode shell were stacked in the order of negative electrode shell-spring sheet-gasket-negative electrode sheet-electrolyte-diaphragm-electrolyte-positive electrode sheet-positive electrode shell, and a button lithium battery was obtained after packaging. The entire assembly process was completed in a glove box filled with argon. The results of the constant current charge and discharge test of the above battery using a charge and discharge instrument show that when the constant current charge and discharge is performed at a rate of 0.2C at room temperature, the first cycle discharge capacity is 188mAh g -1 .

[0120] Comparative Example 2

[0121] 0.688 g LiTFSI and 18 mg CMAB were dissolved in a mixed solution of 2 mL polyethylene glycol methyl ether methacrylate and 400 μL 2,2,3,3,3-pentafluoropropyl acrylate. After stirring and dissolving, the solution was mixed with a conventional ester electrolyte (1 M LiPF 6 in DEC:DMC:EC=1:1:1Vol%with 5% FEC, specifically: mix the three solvents DEC, DMC and EC in equal volumes, add a certain amount of LiPF 6 , configured into a 1 mol / L solution, and then adding a certain amount of FEC so that the mass proportion of the FEC component is 5% of the total) and mixing them in a volume ratio of 1:5 to obtain a quasi-solid electrolyte.

[0122] Preparation of lithium battery:

[0123] The assembly steps of the lithium button battery are the same as those of the above-mentioned comparative example 1, which will not be repeated here.

[0124] The battery was placed at 80°C for 7 hours before charge and discharge tests were performed. A relatively serious self-discharge behavior was observed. At the same time, its transfer impedance was also relatively large, exceeding 300Ω. Comparative Example 2 Compared with the embodiment, the composition of the lithium salt was changed, and LiPF 6 , LiPF 6 During high temperature storage of batteries with electrolytes containing CO 2 The shuttle effect causes serious self-discharge reaction of the battery at high temperature.

[0125] Comparative Example 3

[0126] Preparation of lithium battery:

[0127] 0.574 g of LiTFSI was dissolved in 2 mL of ethoxylated trimethylolpropane triacrylate ETPTA (2.24 g) to form an electrolyte. The assembly steps of the button lithium battery were the same as those of Comparative Example 1 above.

[0128] After testing, the battery can provide almost no capacity at normal temperature and high temperature.

[0129] In summary, the present invention designs a quasi-solid electrolyte that can be polymerized in situ. The polymerized monomers can quickly polymerize into a polymer protective layer at high temperature to prevent internal short circuits and cut off direct contact between electrodes and electrolytes. At the same time, the high boiling point solvents and additives introduced can improve the ionic conductivity and interfacial compatibility of the electrolyte, ensuring the excellent comprehensive performance of the electrolyte. On this basis, with the use of a heat-resistant diaphragm, high energy density positive and negative electrodes, and the synergistic effect of various battery components, new insights are provided for the future application prospects of high-performance and high-safety lithium secondary batteries.

[0130] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

[0131] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0132] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0133] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

Claims

1. A raw material composition for a quasi-solid electrolyte, characterized in that: The raw material comprises the following components: an in-situ polymerization monomer, a lithium salt, an optional solvent, an optional additive and an initiator; wherein, The content of the in-situ polymerized monomer is 20 to 75 wt %; The content of the solvent is 0 to 40 wt%; The content of the initiator is 0.05 to 5 wt%; The content of lithium salt is 6 to 25 wt%; The content of the additive is 0 to 30 wt%.

2. The raw material composition of the quasi-solid electrolyte according to claim 1, characterized in that: In the raw material composition of the quasi-solid electrolyte, The content of the in-situ polymerized monomer is 30 to 75 wt %; The content of the solvent is 0 to 40 wt%; The content of the initiator is 0.05 to 5 wt%; The content of lithium salt is 6 to 25 wt%; The content of the additive is 0 to 30 wt%; Preferably, The content of the in-situ polymerized monomer is 34 to 72 wt %; The content of the solvent is 0 to 10 wt%; The content of the initiator is 0.05 to 1 wt%; The content of lithium salt is 10-25wt%; The content of the additive is 2 to 15 wt%.

3. The raw material composition of the quasi-solid electrolyte according to claim 1, characterized in that: The in-situ polymerization monomer is selected from one or more of acrylate monomers; preferably, the in-situ polymerization monomer is selected from one or more of ethoxylated trimethylolpropane triacrylate, polyethylene glycol methyl ether methacrylate, polyethylene glycol diacrylate, polyethylene glycol methacrylate, 2,2,3,3,3-pentafluoropropyl acrylate; further preferably, the in-situ polymerization monomer is selected from a mixture of polyethylene glycol methyl ether methacrylate and 2,2,3,3,3-pentafluoropropyl acrylate; and / or, The content of the in-situ polymerized monomer is 30 to 40 wt %; and / or, The content of the solvent is 0 to 30 wt %; and / or, The content of the initiator is 0.05 to 1 wt %; and / or, The content of lithium salt is 15-25wt%; and / or, The content of the additive is 1 to 25 wt%.

4. The raw material composition of the quasi-solid electrolyte according to claim 1, characterized in that: The lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluoromethanesulfonyl imide), lithium nitrate, lithium difluorooxalate borate or lithium bis(oxalate borate); preferably, the lithium salt is a mixture of lithium bis(trifluoromethanesulfonyl imide) or lithium difluorooxalate borate and lithium nitrate; and / or, The boiling point of the solvent is ≥200°C; preferably, the solvent is selected from at least one of diethyl carbonate, dimethyl carbonate, ethylene carbonate, propylene carbonate or fluorocarbonate; and / or, The additive is selected from at least one of succinonitrile, vinylene carbonate, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt or 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt; preferably, the additive is selected from a mixture of succinonitrile and vinylene carbonate; and / or, The initiator is selected from at least one of 1-((cyano-1-methylethyl)azo)formamide, azobisisobutyronitrile or dibenzoyl peroxide.

5. A method for preparing a quasi-solid electrolyte raw material composition, characterized in that: The following steps are involved: In a protective atmosphere, a polymerizable monomer, an optional solvent, an optional additive, a lithium salt, and an initiator are uniformly mixed to obtain a quasi-solid electrolyte raw material composition; The quasi-solid electrolyte raw material composition according to any one of claims 1-4 is preferably prepared by the said method.

6. A quasi-solid electrolyte, characterized in that: It is prepared by reacting the quasi-solid electrolyte raw material composition according to any one of claims 1-4 or the quasi-solid electrolyte raw material composition prepared by the method according to claim 5.

7. An application of the quasi-solid electrolyte raw material composition according to any one of claims 1-4 or the quasi-solid electrolyte according to claim 6 in a lithium battery.

8. A lithium battery, characterized in that: The lithium battery includes a negative electrode material, a positive electrode material, the quasi-solid electrolyte according to claim 6, and a separator.

9. The lithium battery according to claim 8, characterized in that: The positive electrode material includes one of a high-nickel ternary positive electrode and a lithium-rich manganese-based oxide positive electrode material; preferably, the high-nickel ternary positive electrode is selected from NCM622 and NCM811; the lithium-rich manganese-based oxide is selected from xLi2MnO3-(1-x)LiTMO2; where 0 < x < 1, and TM is Ni, Co, or Mn; and / or, The negative electrode material is a lithium metal sheet; and / or, The separator is at least one of a polyethylene film, a polypropylene separator, a PP / PE / PP film, a polyimide separator, a ceramic-coated separator, or a poly-p-phenyleneterephthalamide-coated separator.

10. A method for preparing a lithium battery according to any one of claims 8 to 9, characterized in that: It includes the following two methods: Method 1: The preparation of a button-type lithium battery includes the following steps: Stack them in the order of negative electrode case - spring sheet - gasket - negative electrode sheet - separator - positive electrode sheet - positive electrode case. Add the quasi-solid electrolyte raw material composition prepared by the quasi-solid electrolyte raw material composition according to any one of claims 1-4 or the method according to claim 5 on both sides of the separator, and perform encapsulation to obtain a button-type lithium battery; Method 2: The preparation of a soft-pack lithium battery includes the following steps: First, cut the positive electrode sheet and the negative electrode sheet. Connect the electrode tabs to the positive and negative electrodes by spot welding. Then, tightly bond the negative electrode, the separator, and the positive electrode. Seal the battery cell in an aluminum plastic film by heat sealing. Finally, inject the quasi-solid electrolyte raw material composition prepared by the quasi-solid electrolyte raw material composition according to any one of claims 1-4 or the method according to claim 5. After encapsulation, let it stand and be formed, and the preparation of the soft-pack battery is completed.

Citation Information

Patent Citations

  • Wide-temperature-range electrolyte capable of preventing thermal runaway and secondary lithium battery comprising same

    CN109818055A